(untitled) (Journal of Dhaka National Medical College & Hospital, 2016)
Background and objective: Elderly population are increasing with the increased life expectancy at birth. Perhaps no other age group feels the keen sting of loneliness more than the elderly. Institutional settings for the elderly population are developing in our country. This cross sectional study was done to compare the loneliness among elderly living in homes and institutional setting. Materials and method: This was cross sectional analytical study. The study was conducted from 1st January to 31st December 2015 in 5 thanas of Dhaka South and in Old Rehabilitation Centre, Gazipur among three hundred seventy respondents who were above 60 years of age. Data were collected by interviewer administered questionnaires using a University of California Los Angeles Loneliness measuring scale. Descriptive statistics and t-test were computed. Results: The study revealed that more than three quarter (86.5%) respondents were from their own settings. About half (55%) of the respondents living in their own place were female whereas majority of the respondents living in institutional settings were male (60%). The mean age of the respondents was 67.8 years with SD 5.6. In institutional settings more than half (60%) of the respondents were "often felt lonely" whereas 45.6% of respondents living in their own setting "sometimes felt lonely" and this difference was significant (p<0.05). One-third of the respondents 33.8% were feeling loneliness due to death of the spouse. Conclusion: The elderly people living in institutional settings felt more loneliness. It was observed that there was an increasing trend of feeling loneliness with age. So, steps should be taken to take away loneliness of the elderly people J Dhaka National Med. Coll. Hos. 2016; 22 (02): 06-08